PENGARUH KUALITAS MAKANAN, KUALITAS LAYANAN, DAN LINGKUNGAN FISIK RESTORAN TERHADAP KEPUASAN SERTA NIAT BERPERILAKU - anjarsari, gita ekowati; Sri Suprapti, Ni Wayan; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.05.TAHUN 2018, 2018)
The purpose of this study is to explain the effects of food quality, service quality, and physical environment on customer satisfaction and behavioral intention. The sample used are 150 respondents using purposive sampling who have minimal education of senior high school or equal and have been in Nanny’s Pavillon at least twice in the last six months. Data Analyzed using Structural Equation Model (SEM). The results of this study indicate the construct of food quality, service quality, and physical environment has positive and significant effects on customer satisfaction and behavioral intention. The implications on this research show that the customer of Nanny’s Pavillon chooses the food quality such as the catchy food display, variety of the menu, delicious food, also the temperature of the dish as appropriate. The advices for Nanny’s Pavillon managements are to pay more attention to the service,Therefore, the satisfaction of Nanny’s Pavillon customer can be increase so then will effects on behavioral intention in the future.